Implicit assumptions in high potentials recruitment. Issue 6 (4th July 2016) - Posthumus, Jan; Bozer, Gil; Santora, Joseph C.
Abstract : Purpose: Professionals of human resources (HR) use different criteria in practice than they verbalize. Thus, the aim of this research was to identify the implicit criteria used for the selection of high-potential employees in recruitment and development settings in the pharmaceutical industry. Design/methodology/approach: A semi-structured interview guide was developed and used to collect data from 15 European and US recruiters in the pharmaceutical sector. The interview guide included an embedded association test to identify potential differences between implicit assumptions about high potentials and verbalized criteria among participants. Findings: These include differences and similarities between the criteria to define high potentials and the implicit assumptions HR professionals use in their initial selection of employees who are selected for further assessment and development programmes. Research limitations/implications: Size of the sample is a limitation. Therefore, the conclusions drawn from this study should be treated with a degree of caution. Practical implications: Learning how HR professionals use implicit assumptions about potential recruits should inform practitioners about selection, promotion and training strategies. Given the increasing application of automated search algorithms to identify and select high potentials for recruitment, development and promotion purposes, future studies should account for the differences between used and verbalized criteria underlying the development of these systems. Originality/value: This study shows how the used implicit assumptions of HR professionals about high potentials differ from verbalized statements and guidelines.